Hybrid biochar-graphitic carbon nitride (g-C3N4) composite photocatalyst: a facile strategy for enhanced degradation of Ciprofloxacin (CIP) - Ijlal Idrees; Muhammad Zafar; Malik Adeel Umer; Amna Mir; Fahad Rehman; Abrar Faisal; Abdul Razzaq; Woo Young Kim (Materials Research Express)
Amongst the diversity of pharmaceutical micropollutant degradation methods and to counter the possible hazards posed by these micropollutants economically and sustainably, a new approach of wastewater treatment involving advanced oxidation process (AOP) like photocatalysis offers a viable and economical treatment of micropollutants in wastewater. Amongst a variety of photocatalysts, the one that emerged as the most economical, abstemiously thermally stable, innocuous, and resourceful semiconductor photocatalyst is graphitic carbon nitride (GCN). Hence, bearing in mind these aspects together with the simplistic preparation approach and visible light absorption of GCN, a composite of GCN with Biochar (BC) is prepared in this contemporary research work aiming towards enhanced degradation of Ciprofloxacin (CIP) through improved visible light absorption and good photoexcited electron–hole separation. The enhancement in the photocatalytic activity of GCN is achieved by changing the quantity of BC. This alteration in BC content led to the creation of an optimum sample with the best degradation efficiency towards CIP. The superlative removal efficiency with 75% removal of CIP was exhibited by the 0.22-BGCN sample whose removal efficiency was noted to be 3.5 times higher than GCN (21%). These results point towards the success of composite formation of GCN with BC due to enhanced photocatalytic activity observed in the results and prove the creation of a visible light active (VLA) photocatalyst for efficient removal of pharmaceutical micropollutants like CIP from wastewater. Many different methods are employed to study the physiochemical, textural, and optical properties of the prepared material which include Brunauer–Emmett–Teller (BET) surface area, x-ray diffraction spectroscopy (XRD), Scanning electron microscopy (SEM), Fourier Transform Infrared (FTIR) spectroscopy, UV Visible absorption, and Photoluminescence (PL) spectroscopy.